Characterization Of Aerophytic Oxyphototrophs Isolated From Gua Tempurung, Malaysia: Polyphasic And Biochemical Approaches - Abdullahi, Zulaihat Hamza (2024)
Caves are among the extreme oligotrophic environments with limited nutrients and low light intensity, but some aerophytic microalgae find this environment suitable for their growth and survival. Gua Tempurung is the largest limestone caves in Malaysia, but unfortunately no study was conducted on its algal diversity, taxonomic information, adaptation, physiological, and biochemical composition. This study aimed to assess the characteristics and adaptation of aerophytic oxyphototrophs isolated from Gua Tempurung.